Visualizing and assessing hypotheses in marine archaeology in a vr cave environment - Κατσουρή, Ειρήνη Μαρίτσα (Τμήμα Πολυμέσων και Γραφικών Τεχνών,Σχολή Καλών και Εφαρμοσμένων Τεχνών,Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The understanding and reconstruction of a wreck’s formation process can be a complicated procedure that needs to take into account many interrelated components and has not been adequately and precisely investigated in the past. The Cypriot archaeologists investigating the 4th century BC, Mazotos shipwreck are unable to interact easily and intuitively with the recorded data, a fact that impedes visualization and reconstruction and subsequently delays the evaluation of their hypotheses. An immersive 3D visualization application that utilizes a VR Cave is developed, with the intent to enable researchers to mine the wealth of information this ancient shipwreck has to offer. Through the implementation and evaluation of the proposed application, this research seeks to investigate whether such an environment can aid the interpretation and analysis process and ultimately serve as an additional scientific tool for marine archaeology.
Keywords: VR Cave; Αrchaeology